Investigation of the Frequency and Distribution of Beta-Lactamase Genes in the Clinical Isolates of Acinetobacter baumannii Collected From Different Regions of Turkey: A Multicenter Study - Beris, Fatih Saban; Budak, Emine Esra; Gulek, Duygu; Uzun, Aytul; Cizmeci, Zeynep; MENGELOĞLU, FIRAT ZAFER; DİREKEL, ŞAHİN; ÇETİNKOL, YELİZ; Ay Altintop, Yasemin; Iraz, Meryem; Dal, Tuba; Say Coskun, Safiye Umut; et al. (My University, 2016)
The diversity and distribution of TEM, SHV and CTX-M type of extended-spectrum beta-lactamases (ESBLs) are important for the treatment and control of infections. Determination of ESBL genes in clinical isolates by polymerase chain reaction (PCR) and DNA sequencing can obtain useful data for their molecular epidemiology and risk. The aim of this study was to investigate the frequency of beta-lactamase genes in Acinetobacter baumannii strains isolated from different regions of Turkey. A total of 519 A. baumannii strains collected from hospitals located at 12 different provinces of Turkey (Bolu (n=67), Tokat (n=47), Trabzon (n=25), Ordu (n=27), Diyarbakir (n=47), Nigde (n=31), Kayseri (n=36), Ankara (n=41), Kirikkale (n=26), Kahramanmaras (n=25), Mersin (n=40), Istanbul (n=107)] between 2011-2012 period were included in the study. Identification of the isolates were performed by both conventional methods and automated systems, VITEK2 Compact (BioMerieux, France) and API 32GN (BioMerieux, France). Disc diffusion method was used for the detection of antibiotic susceptibilities of the isolates and the results were evaluated according to CLSI (Clinical and Laboratory Standards Institute) criteria. Tigecycline and colistin sensitivities of the isolates were evaluated according to BSAC (British Society for Antimicrobial Chemotherapy) criteria. The presence of beta-lactamase genes, namely bla(oxa-51), bla(TEM), bla(SHV), bla(CTX-M1), bla(CTX-M2), bla(GES) and bla(VIM) were detected by PCR. In our study, the resistance rates against colistin, tigecycline, ampicillin-sulbactam, amoxicillin-clavulanic acid, cefoperazone/sulbactam, tobramycin, ceftriaxone, piperacillin-tazobactam, gentamicin, ampicillin, tetracycline, cefepime, piperacillin, amikacin, trimethoprim-sulfamethoxazole, meropenem, levofloxacin, ciprofloxacin, imipenem and ceftazidime were detected as; 0.6%, 2.7%, 11.9%, 15.2%, 21%, 22.9%, 23.9%, 48.6%, 59.5%, 61.8%, 66.3%, 67.8%, 69.2%, 71.1%, 77.5%, 78.6%, 81.1%, 82.9%, 87.5% and 89.4%, respectively. All of the isolates (100%) were OXA-51 positive, while 443 (85.4%) out of 519 strains harbored other beta-lactamase genes searched in the study. When the distribution of the genes were evaluated, bla(TEM-1) was found as the predominant one with a frequency rate of 55.7% (n=289/519), followed by bla(CTX-M2) (63/519, 12.1%), bla(CTX-M1) (42/519, 8.1%), bla(SHV) (40/519, 7.7%), bla(GES) (8/519, 1.5%) and bla(VIM) (1/519, 0.2%). Cooccurence of ESBL genes was detected in 16.3% (72/443) of the strains, being mostly TEM+CTX-M2 (20/72, 27.8%), TEM+SHV (11/72, 15.3%) and TEM+CTX-M1 (10/72, 13.9%). In addition, it was noted that the distribution of ESBL genes between isolates showed differences according to the provinces. Accordingly, none of the strains isolated from four provinces (Bolu, Nigde, Mersin, Kahramanmaras) and from three provinces (Bolu, Kahramanmaras, Diyarbakir) harbored bla(CTX-M1/M2) and bla(SHV) genes, respectively. The bla(TEM) gene was detected in isolates collected from all of the provinces, with a highest frequency in Nigde (28/31, 90.3%) and lowest in Trabzon (1/25, 4%). The presence of GES-11 type ESBLs was found only in the isolates sent from Nigde province (8/31; 25.8%). Screening of metallo-beta-lactamase VIM gene also yielded a single positive result amongst only Nigde isolates (1/31; 3.2%), and this gene was identified as VIM-5 type by DNA sequencing.